A Case Report of an Atypical Presentation of IgG4-Related Disease and Idiopathic CD4 Lymphocytopenia - Francesco Rapisarda; Luca Zanoli; Grazia Portale; Salvo Scuto; Pietro Castellino (Case Reports in Medicine)
The IgG4-related disease is a fibroinflammatory disease characterized by tumefactive lesions, a dense lymphoplasmacytic infiltrate rich in IgG4-positive plasma cells, storiform fibrosis, and, often but not always, elevated serum levels of IgG4. Idiopathic CD4 lymphocytopenia is a heterogenic and rare syndrome characterized by the detection of a persistent absolute CD4 T cells count <300 cells/mm3 (or <20% of total T cells) in more than one occasion and no evidence of HIV infection in absence of immunodeficiency or therapy associated with depressed levels of CD4 T cells. We report the case of a 50-year-old man with a multiorgan IgG4-related disease presenting in a temporal association with a profound and symptomatic idiopathic CD4 lymphocytopenia. Both clinical pictures improved after steroid treatment. Idiopathic CD4 lymphocytopenia has been associated with a number of autoimmune conditions but, to the best of our knowledge, this is the first case in which an association with the IgG4-related disease is reported.